-4(5z-6)=24+8z

Simple and best practice solution for -4(5z-6)=24+8z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(5z-6)=24+8z equation:


Simplifying
-4(5z + -6) = 24 + 8z

Reorder the terms:
-4(-6 + 5z) = 24 + 8z
(-6 * -4 + 5z * -4) = 24 + 8z
(24 + -20z) = 24 + 8z

Add '-24' to each side of the equation.
24 + -24 + -20z = 24 + -24 + 8z

Combine like terms: 24 + -24 = 0
0 + -20z = 24 + -24 + 8z
-20z = 24 + -24 + 8z

Combine like terms: 24 + -24 = 0
-20z = 0 + 8z
-20z = 8z

Solving
-20z = 8z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-8z' to each side of the equation.
-20z + -8z = 8z + -8z

Combine like terms: -20z + -8z = -28z
-28z = 8z + -8z

Combine like terms: 8z + -8z = 0
-28z = 0

Divide each side by '-28'.
z = 0

Simplifying
z = 0

See similar equations:

| 2c+4c=4 | | .52=log(x) | | 1/4(8-2h)+.5h=.25h | | 2w+2(2w-3)=6 | | 2(-3x+8)=-44 | | 12+6x=24 | | 3xn+7=52 | | -5(2x+9)=65 | | 7x=36-x | | log(x+3)=1-log(x) | | 5x+1=3x+8+2x-7 | | 6x-8=x+47 | | 6c+21=17c+10 | | 5x+6=3x+8+2x-7 | | 5x+5=3x+8+2x-7 | | 4a+5=15 | | 18a+3= | | 0.5y^3=13.5 | | 56=-13 | | 15x-20=70 | | X+4=28-x | | x(3x-15)=0 | | -7x+5=-x-1 | | 5-0.8(d-18)=0.4(12d-18) | | 3-3x=x+47 | | 81x^2=126x-49 | | (x+9)(x-1)= | | 2x+7=-3+5x | | 5x+15=3x+8+2x-7 | | 3y-13+2y-12=180 | | 2t-83+2t-51=180 | | 14y-6=5 |

Equations solver categories